Gangguan Kepribadian Narsistik dan Implikasinya Terhadap Kesehatan Mental - Dewi Purnama Sari (Islamic Counseling : Jurnal Bimbingan dan Konseling Islam, 2021)
On the one hand, the development of social media can provide convenience to the community, both in communication, in developing science and in the economic aspect. But on the other hand, the development of social media also has a negative impact on society. One of the negative impacts of using social media is that it can cause personality disorders, give birth to narcissistic attitudes and behaviors and can interfere with mental health. This study aims to describe the narcissistic personality disorder, the symptoms of a person experiencing narcissistic personality disorder, efforts to overcome narcissistic personality disorder and the relationship between narcissistic personality and mental health. The method used is a research library. The data collection technique used document study, then analyzed using content analysis. The results of the discussion show that narcissistic personality disorder is basically a personality disorder caused by a person's excessive attitude or behavior in seeing himself. If the narcissistic personality causes disruption of life functions, it will have the potential to disrupt mental health.